Avaliação da expressão do receptor de produtos finais de glicação avançada (RAGE) no carcinoma inflamatório da mama - Coelho, Mariana Timbaúba Benício (2024)
InflammatoryBreast Carcinoma (IBC) is a clinicallyaggressivemanifestationofbreastcancercharacterizedbysignsofinflammation, whichcomplicatesearlydiagnosis, andbyrapidprogressionandlowsurvival rates. Additionally, IBC mayexhibitdistinctcharacteristics, such as alteredcellularsignalingpathwaysand a higherfrequencyofsomaticmutations. In thiscontext, the Receptor for AdvancedGlycationEnd-products (RAGE) emerges as a significantfactor, showing high expression in aggressivetumorslike triple-negative carcinoma, whichisalsoassociatedwithworseclinicaloutcomes. Thisstudyaimstoevaluate RAGE expressionand its associationwith tumor aggressivenessmarkers in patientswith IBC. Thisis a cross-sectionalstudyinvolving a case groupand a controlgroup, includingsamplesfrom IBC and non-inflammatorybreast carcinoma (non-IBC) from 34 patientswithhistopathological diagnoses, recruitedbetween 2015.1 and 2020.2 at Haroldo Juaçaba Hospital/CancerInstituteof Ceará, comprising 18 diagnosedwith IBC and 16 with non-IBC. Histopathologicalsectionsof 3 µm werepreparedonsignalized slides, followedbyimmunofluorescencewithpolyclonalanti-RAGEantibody, and RAGE expressionwassemi-quantifiedusingtheImage J/FIJI software. Clinical, epidemiological, andpathological data werecollectedandstatisticallyanalyzedusing SPSS software, applyingtests for comparisonsbetweengroups. ThisstudywasapprovedbytheEthicsCommitteeoftheCancerInstituteof Ceará under No. 5.010.710. Resultswereexpressedwithstatisticalsignificance (p<0.05). A higherlevelof RAGE expressionwasobserved in associationwith Ki67 (p=0.034) andthe TNBC subtype (p=0.026) in patientswith IBC comparedtothe non-IBC group. Photomicrographsofthebiopsiesrevealedinfiltrativenichesandprominentnucleoliindicativeof high-grade invasiveductal carcinoma. The RAGE immunofluorescenceanalysisshowedincreasedexpression (107.4 ± 37.9) in the IBC groupcomparedto non-IBC samples (78.4 ± 42.2). Therefore, it isconcludedthat RAGE expressionisassociatedwith a higherproliferation index andthe triple-negative molecular subtype, whichisconsidered more aggressiveandhas a poorerprognosis, highlightingtherelevanceofthis receptor in clinicalpracticeand its potential as a biomarker.